The Social Implication of Stigma on Divorcees in Sasak Society: A Phenomenological Study in Lombok Tengah - Riska Mutiah; Muhammad Syarifudin (University of Muhammadiyah Malang, 2024)
Women who identify as divorcees are frequently marginalized and treated as second-class citizens within society. Preliminary findings from this study reveal that divorcees encounter significant hardships resulting from stigmatization post-divorce. This stigmatization not only leads to social contempt but also exposes divorcees to verbal and even sexual violence from individuals around them. This research employs a qualitative phenomenological approach to explore (1) the manifestations of stigma against divorcees and (2) the social consequences of divorcee stigma within the Sasak community in Kec. Kopang, Kab. Lombok Tengah. The findings indicate that (1) divorcees face stigma from their communities, experiencing social contempt and ridicule due to their status. Additionally, some participants reported instances of sexual harassment, including receiving inappropriate images via chat from several male acquaintances, one of whom was a relative. Catcalling was also identified as a form of harassment. (2) The presence of this stigma has notable social implications by developing mechanisms of social distancing. The divorcees tend to distance themselves from others through two main strategies: reducing social interactions and by developing a resilient mentality towards the stigma, especially for those who must engage with others for professional reasons.